Factors predicting loss of cervical lordosis following cervical laminoplasty: A critical review - Alam, Intekhab (J Craniovertebr Junction Spine, 2020)
BACKGROUND: Laminoplasty is a method of posterior cervical decompression which indirectly decompresses the spinal column. Unfortunately, many patients undergoing laminoplasty develops postoperative loss of cervical lordosis (LCL) or kyphotic alignment of cervical spine even though they have sufficient preoperative lordosis which results in poor surgical outcome. OBJECTIVE: We would like to highlight the relationship between various radiological parameters of cervical alignment and postoperative LCL in patients undergoing laminoplasty. METHODS: We performed extensive literature search using PubMed, Google Scholar, and Web of Science for relevant articles that report factors affecting cervical alignment following laminoplasty. RESULTS: On reviewing the literature, patients with high T1 slope have more lordotic alignment of cervical spine preoperatively. They also have more chances of LCL following laminoplasty. C2–C7 sagittal vertical axis (SVA) has no role in predicting LCL following laminoplasty though patients with low T1 slope (≤20°) and high C2–C7 SVA (>22 mm) had correction of kyphotic deformity following laminoplasty. C2–C7 lordosis, Neck Tilt, cervical range of motion, and thoracic kyphosis has no predictive value for LCL. Lower value of T1 slope (T1S-CL) and CL/T1S has more incidence of developing LCL following laminoplasty. The role of C2–C3 disc angle has not yet been evaluated in patients undergoing laminoplasty. Dynamic extension reserve determines the contraction reserve of SPMLC and lower dynamic extension reserve is associated with higher chances of LCL following laminoplasty. CONCLUSIONS: Cervical lordotic alignment is important in maintaining cervical sagittal balance which ultimately is responsible for global spinal sagittal balance and horizontal gaze. Among various radiological parameters, T1 Slope has been reported to be the most important factor affecting cervical alignment following laminoplasty.